Structure of mixed anionic/nonionic surfactant micelles: experimental observations relating to the role of headgroup electrostatic and steric effects and the effects of added electrolyte. - Penfold, J; Tucker, I; Thomas, R; Staples, E; Schuermann, R (2005)
The structures of the mixed anionic/nonionic surfactant micelles of SDS/C12E6 and SDS/C12E8 have been measured by small angle neutron scattering (SANS). The variations in the micelle aggregation number and surface charge with composition, measured in D2O and in dilute electrolyte, 0.01 and 0.05 M NaCl, provide data on the relative roles of the surfactant headgroup steric and electrostatic interactions and their contributions to the free energy of micellization. For the SDS/C12E8 mixture, solutions increasingly rich in C12E8 show a modest micellar growth and an increase in the surface charge. The changes with increasing electrolyte concentration are similarly modest. In contrast, for the SDS/C12E6 mixture, solutions rich in C12E6 show a more significant increase in aggregation number. Furthermore, electrolyte has a more substantial effect on the aggregation for the nonionic (C12E6) rich mixtures. The experimental results are discussed in the context of estimates of the steric and electrostatic contributions to the free energy of micellization, calculated from the molecular thermodynamic approach. The variation in micelle surface charge is discussed in the context of the "dressed micelle" theory for micelle ionization, and other related data.